Identification of novel EZH2 inhibitors through pharmacophore-based virtual screening and biological assays. Issue 15 (1st August 2016) - Wu, Yunlong; Hu, Junchi; Ding, Hong; Chen, Limin; Zhang, Yuanyuan; Liu, Rongfeng; Xu, Pan; Du, Daohai; Lu, Wenchao; Liu, Jingqiu; Liu, Yan; Liu, Yu-Chih; et al.
Graphical abstract: Abstract: Polycomb repressive complex 2 (PRC2) acts as a primary writer for di- and tri-methylation of histone H3 at lysine 27. This protein plays an essential role in silencing gene expression. Enhancer of zeste 2 (EZH2), the catalytic subunit of PRC2, is considered as a promising therapeutic target for cancer. GSK126, a specific inhibitor of EZH2, is undergoing phase I trials for hypermethylation-related cancers. In addition, many derivatives of GSK126 are also commonly used in laboratory investigations. However, studies on the mechanism and drug development of EZH2 are limited by the absence of structural diversity of these inhibitors because they share similar SAM-like scaffolds. In this study, we generated a pharmacophore model based on reported EZH2 inhibitors and performed in silico screenings. Experimental validations led to the identification of two novel EZH2 inhibitors, DCE_42 and DCE_254, with IC50 values of 23 and 11 μM, respectively. They also displayed significant anti-proliferation activity against lymphoma cell lines. Thus, we discovered potent EZH2 inhibitors with novel scaffold using combined in silico screening and experimental study. Results from this study can also guide further development of novel specific EZH2 inhibitors.